Delayed Cognitive Abnormalities and Frontal Lobe Damage - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
The consequences of early frontal lobe damage, restricted to the polar and mesial portion of the left prefrontal cortex and deep white matter, on higher cognitive and psychologic development are reported in a 33-year-old woman who sustained injury at 7 years of age and was evaluated at the Division of Behavioral Neurology and Cognitive Neuroscience, University of Iowa College of Medicine, Iowa City.